Comparison of Oral Health Status and Behaviors Between Children with Autistic Spectrum Disorder and Healthy Children in Rasht City, Iran - Seyedeh Hediyeh Daneshvar; Alaleh Kavianfar; Seyed Hossein Masoomi; Mir Mahdi Daneshvar (Cumhuriyet University, 2020)
Objectives: In this study, the caries experience, gingivitis and behaviors of 6-12 year old children with Autistic Spectrum Disorder (ASD) were investigated according to the Frankl scale during dental examination, and then compared with healthy children.Materials and Methods: Totally, 55 children with ASD (including 49 males and 6 females) and 165 healthy children (including 83 males and 82 females) were assessed in Rasht, Iran. Before clinical examination, their parents were asked to complete a questionnaire consisting of several questions about parental education level, nutritional status and oral hygiene status. The number of decayed, missing and filled teeth, gingival status and behaviors of the children were recorded during the dental examination. The obtained data were analyzed using Chi-square and Mann Whitney U Test. P-value less than 0.05 was considered statistically significant.Results: Our results implied that the children with ASD had higher DMFT/dmft scores compared with healthy children (p<0.001). Also, the prevalence of localized and generalized gingivitis was higher in children with ASD than that in healthy children (p=0.014). Most of the children with ASD behaved in negative or definitely negative manner during dental examination (p=0.001). The results showed that the mean level of parental education and oral hygiene habits (such as frequency of brushing and flossing) in healthy children were higher than that in the children with ASD.Conclusions: According to the results, the children with ASD had higher caries experience and gingivitis compared with healthy children and most of them behaved in negative or definitely negative manner during dental examination.